Mapping the experiences of people with achalasia from initial symptoms to long‐term management - Melika Kalantari; Amelia Hollywood; Rosemary Lim; Majid Hashemi (Wiley, 2021)
Abstract Background Achalasia is a rare motility disorder affecting the oesophagus, which is associated with a range of symptoms and different treatment strategies. Currently, little is known about people's experiences with achalasia and its management. This study aimed to understand the experiences of people living with achalasia, from the initial onset of symptoms to long‐term management. Method This qualitative study explored the journey of people living with achalasia and outlined the care pathway using a process map. Ten female and five male participants living with achalasia (age range: 40‐73) took part, and all aspects of their diagnosis, treatment and management were discussed. A process map showing people's experiences by separating the management of their condition into a series of steps was developed to present the pathway in the participants' journey. The analysis involved discussing the process map within the research team. Results The process map comprised of 10 steps, which occurred before and after diagnosis. The developed map indicates that most participants managed their on‐going symptoms through stress management techniques and dietary changes. Key issues that participants highlighted about their journey managing achalasia were misdiagnosis, delay in diagnosis and lack of support in the long‐term management of achalasia. Conclusions This research was a novel study exploring patients' experiences and management of achalasia and mapping their journey. Two distinct phases to their journeys were identified: before and after diagnosis. Areas highlighted by this study can provide a basis for future research, in particular behaviour change to support the long‐term management of achalasia.